New data on the poorly-known European Late Jurassic turtles "Thalassemys" and "Enaliochelys" and description of a new basal eucryptodiran taxon - Pérez-García, A. (Journal of Iberian Geology, 2015)
One of the most abundant clades of turtles in the Late Jurassic record of Europe is Eucryptodira, represented by Plesiochelyidae, Eurysternidae, Hylaeochelys and Thalassemys. The detailed study of a British specimen preliminarily attributed to the plesiochelyid “Pelobatochelys” allows this attribution to be refuted. Rather, it is recognized as the only confirmed specimen of the genus Thalassemys outside Central Europe. The diversity of Eucryptodira in the Late Jurassic of Europe is here increased, thanks to the revision of two problematic specimens, not assignable to any of the four above mentioned taxa. Enaliochelys chelonia, is a poorly-known British taxon ignored since the late nineteenth century because of its putative synonymy with Thalassemys hugii. The validity of this taxon is supported here and a diagnosis for it is proposed for the first time. The other specimen, from France (Oléron Island), was previously attributed to “Thalassemys moseri”, which is currently considered invalid. It is recognized as a representative of a new taxon, Jurassichelon oleronensis gen. et sp. nov.